Carboxypeptidase D is the only enzyme responsible for antibody C‐terminal lysine cleavage in Chinese hamster ovary (CHO) cells. Issue 10 (6th April 2016) - Hu, Zhilan; Zhang, Henry; Haley, Benjamin; Macchi, Frank; Yang, Feng; Misaghi, Shahram; Elich, Joseph; Yang, Renee; Tang, Yun; Joly, John C.; Snedecor, Bradley R.; Shen, Amy
ABSTRACT: Heterogeneity of C‐terminal lysine levels often observed in therapeutic monoclonal antibodies is believed to result from the proteolysis by endogenous carboxypeptidase(s) during cell culture production. Identifying the responsible carboxypeptidase(s) for C‐terminal lysine cleavage in CHO cells would provide valuable insights for antibody production cell culture processes development and optimization. In this study, five carboxypeptidases, CpD, CpM, CpN, CpB, and CpE, were studied for message RNA (mRNA) expression by qRT‐PCR analysis in two most commonly used blank hosts (DUXB‐11 derived DHFR‐deficient DP12 host and DHFR‐positive CHOK1 host), used for therapeutic antibody production, as well an antibody‐expressing cell line derived from each host. Our results showed that CpD had the highest mRNA expression. When CpD mRNA levels were reduced by RNAi (RNA interference) technology, C‐terminal lysine levels increased, whereas there was no obvious change in C‐terminal lysine levels when a different carboxypeptidase mRNA level was knocked down suggesting that carboxypeptidase D is the main contributor for C‐terminal lysine processing. Most importantly, when CpD expression was knocked out by CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) technology, C‐terminal lysine cleavage was completely abolished in CpD knockout cells based on mass spectrometry analysis, demonstrating that CpD is the only endogenous carboxypeptidase that cleaves antibody heavy chain C‐terminal lysine in CHO cells. Hence, our work showed for the first time that the cleavage of antibody heavy chain C‐terminal lysine is solely mediated by the carboxypeptidase D in CHO cells and our finding provides one solution to eliminating C‐terminal lysine heterogeneity for therapeutic antibody production by knocking out CpD gene expression. Biotechnol. Bioeng. 2016;113: 2100–2106. © 2016 Wiley Periodicals, Inc.